PENGARUH PENERAPAN TATA KELOLA PEMERINTAHAN YANG BAIK DAN TEKNOLOGI INFORMASI TERHADAP KINERJA SATUAN KERJA PERANGKAT DAERAH (SKPD) GUNA MENDUKUNG IMPLEMENTASI OTONOMI DAERAH - Edy Suprianto (Jurnal Ekonomi dan Bisnis, 2014)
The purposes of reserach are to creat the effectiveness and efficiency of pubic services. So It need increase of good government governance innovation with support from strategic human resources management empowerment and good information technology. The research population is all of government official in Demak City. The samples are choosed by used random sampling. To test data is used Metode Path analysis (SEM) as quantitaive analyse and qualitative analyse. We got 60 respondents from 10 government official in Demak city. Based on the data analyse, we can note that all of variable in this research (meaning, competence,self determination, locus of control, impact dan good governance) effect positive significanly on Government offical performance. While variable of teknologi informasi is not effect significantly on Government offical performance.Keywords: Good Governance, information Technology, Public service and Government offical performance